1978
DOI: 10.1002/pssa.2210480232
|View full text |Cite
|
Sign up to set email alerts
|

Gold solubility in silicon and gettering by phosphorus

Abstract: A simple model for gettering of gold by phosphorus a t low concentration is proposed. This model assumes that gold is dissolved in single vacancies for intrinsic silicon, and in vacancies paired with phosphorus atoms for doped silicon. Low concentration gettering is directly compatible with MOS technology and allows leakage current in diodes to be reduced of about three orders of magnitude.Nous allons proposer un model pour decrire la capture de l'or par le phosphore. Xotre model est base sur l'hypothhse que l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In segregate-induced gettering, the solid solubility of metallic impurities in the gettering sinks increases substantially more than in silicon crystal bulk without gettering sinks [51]. Figure 6 indicates that the metallic impurity concentration in the hydrocarbon–molecular–ion projection range is higher than that in the solid solubility solution of silicon crystal bulk.…”
Section: Resultsmentioning
confidence: 99%
“…In segregate-induced gettering, the solid solubility of metallic impurities in the gettering sinks increases substantially more than in silicon crystal bulk without gettering sinks [51]. Figure 6 indicates that the metallic impurity concentration in the hydrocarbon–molecular–ion projection range is higher than that in the solid solubility solution of silicon crystal bulk.…”
Section: Resultsmentioning
confidence: 99%
“…For the first possibility, a previous study showed that a high‐energy ion implantation technique formed ion‐ implantation‐related induced defects in the implantation projection range . These defects induced strain stress in the silicon matrix interface.…”
Section: Resultsmentioning
confidence: 99%
“…Metal impurities elimination efficiency of P gettering depends on the transport of impurities and solubility segregation. It was reported that there is competing effectiveness of two processes responsible for segregation gettering, that is, impurity transport and solubility segregation, the latter process being characterized by a decreasing segregation coefficient with increasing temperature [8,11]. At high temperature, metal solubility is large, so required time for precipitation at the gettered region becomes long.…”
Section: Resultsmentioning
confidence: 99%